2015
DOI: 10.1016/j.biomaterials.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected high photothemal conversion efficiency of gold nanospheres upon grafting with two-photon luminescent ruthenium(II) complexes: A way towards cancer therapy?

Abstract: The design and development of functional hybrid nanomaterials is currently a topic of great interest in biomedicine. Herein we investigated the grafting of Ru(II) polypyridyl complexes onto gold nanospheres (Ru@AuNPs) to improve the particles′ near infrared (NIR) absorption, and ultimately allow for application in photothermal cancer therapy.As demonstrated in this article, these ruthenium(II) complexes could indeed significantly enhance gold nanospheres' two-photon luminescence (PTL) intensity and phototherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…25A). 286 The Ru@AuNPs converted NIR (808 nm) light to heat (ΔT = 9.4–38.5 °C), with high photothermal therapy efficiency (ΔT = 38.5 °C, η = 33.3%), which was well over the required temperature increase for efficient cancer photothermal therapy. More importantly, the in vivo experiments indicated that Ru@AuNPs , as PTT compounds, had significant tumor ablation efficacy.…”
Section: Ruthenium(ii)-based Nanomaterials Systemsmentioning
confidence: 95%
See 2 more Smart Citations
“…25A). 286 The Ru@AuNPs converted NIR (808 nm) light to heat (ΔT = 9.4–38.5 °C), with high photothermal therapy efficiency (ΔT = 38.5 °C, η = 33.3%), which was well over the required temperature increase for efficient cancer photothermal therapy. More importantly, the in vivo experiments indicated that Ru@AuNPs , as PTT compounds, had significant tumor ablation efficacy.…”
Section: Ruthenium(ii)-based Nanomaterials Systemsmentioning
confidence: 95%
“…Indeed, under diode laser (808 nm) irradiation at the power density of 0.8 W/cm 2 for 5 min, tumors shrunk gradually or disappeared individually after 10 days of treatments. 286 This study with Ru(II) complex modifications provides an effective solution for overcoming the typically poor NIR absorbance and low photostability (melting effect) of gold nanoparticles in PTT. Recently, the same group developed two novel gold nanostructures to get the Ru(II)-functionalized gold nanorods, ( AuNRs@Ru ) and nanostars ( AuNTs@Ru ) (see Fig.…”
Section: Ruthenium(ii)-based Nanomaterials Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…The employment of near-infrared (NIR) radiations in photothermal therapy (PTT) to treat cancer is current high pitched interest aside from its classical applications such as telecommunication, sensing ablation etc [1,2]. The reason is that NIR region (700–1100 nm) is ideal clinical phototherapeutic window for PTT as attenuation of NIR radiations by skin, blood and tissues is low and it allow for the treatment of deep-seated tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been attempting to find a perfect match to gold and ligand complexes with fewer side effects [33][34][35][36][37][38][39]. Antitumor activities of new gold(III) complexes with 1,2-diaminocyclohexane were estimated in prostate cancer and gastric carcinoma by Al-Jaroudi et al [40].…”
Section: Discussionmentioning
confidence: 99%